ANALISIS KONSTRUKSI SOSIAL: PENENTUAN SEKOLAH PADA ANAK USIA DINI OLEH ORANG TUA MILENIAL DI KECAMATAN KARTASURA - Dina Wanda Purnama; Bagas Narendra Parahita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Examining the phenomenon of growing private school enrollment compared to public schools, this study seeks to uncover the reasons millennial parents in Kartasura District select particular schools for their children. Peter L. Berger's social construction theory provides the framework for understanding these choices. Berger's perspective suggests that social reality, rather than being objective, is formed through a dialectical process involving externalization, objectification, and internalization. Applied to educational selection, this means that millennial parents socially construct their perceptions of "school quality," "child achievement," and the "ideal environment." The research methodology is a qualitative descriptive phenomenological type, with data collected through direct observation, in-depth interviews, and documentation.. The results of the study show several factors, namely: 1) Millennial parents believe that private schools have a more innovative curriculum, more complete infrastructure and have well-qualified teachers. 2) The development of character and non-academic skills becomes more focused through the provision of extracurricular activities from various fields. The study found that millennial parents’ decisions about private schools were influenced by a combination of factors including educational quality, holistic development, conducive environment and social perceptions, although financial implications were also a significant factor.